Karl Polanyi and the Law of Market Society - Frerichs, Sabine (Österreichische Zeitschrift für Soziologie, 2019)
Karl Polanyi started his career as a doctor of law and practiced law for a while; but he did not become a legal scholar. As an economic historian, anthropologist, or sociologist, he was concerned with the relation of economy and society. But even though law is an important factor in mediating this relationship, Polanyi gave little attention to the law as such. As part of an endeavour to advance a ‘Polanyian’ economic sociology of law, this article develops the ‘law of market society’ as an analytical category. For this purpose, three argumentative strategies are combined. First, the article draws on The Great Transformation to reconstruct the role of law in the processes of commodification and decommodification. Second, it turns to Marxist scholarship to explore the conceptual link between law and economics and to ponder to what extent law itself can become a commodity. Third, it links Polanyi’s approach with American institutionalism, and Commons’ work in particular, to show how the evolution of the ‘law of market society’ can also be understood as a collective enterprise which continuously evolves. It is argued that these perspectives complement each other and help to bring the law back in where it is missing.
Keywords: law of market society; sociology of law

Neoliberal Legality as Dual Process: Embeddedness, Courts and Crime Prevention in the United States - Campeau, Holly; Levi, Ron (British Journal of Criminology, 2019)
This article advances research on 'neoliberal legality' to focus on the role of courts in response to neoliberal crime prevention approaches. Drawing on Karl Polanyi's analysis of embeddedness in market capitalism, along with criminological research on the penal state, we analyse three case studies reflecting central crime prevention approaches of the neoliberal era in the United States. We find that neoliberal legality is more complex than simply legitimating or resisting neoliberal policies. We highlight how courts did both at once—they moderated the harshest edges of neoliberal policies through alternative symbolic frames, yet in so doing also legitimated the core of neoliberal crime prevention efforts. We argue that neoliberal legality operates through this dual process, in which the basic thrust of neoliberalism is legitimated by also having policies moderated, recast and embedded within other social and juridical expectations.
Keywords: POLANYI, Karl, 1886-1964; United States; capitalism; courts; crime prevention; embeddedness (socioeconomic theory); law; neoliberal legality; neoliberalism; penal state

Who Plans Our Political Economy? A Solidarity Economy Vision for Democratic Political Economy Planning - Gilbert, Geoff (Harvard Unbound, 2019)
The Democratic Party's current left-wing resurgence shows that significant popular support exists for an expanded vision of fundamental rights for all people: rights to public health care and higher education; affordable housing; living-wage jobs; and a Green New Deal that transitions human society to ecological sustainability while also reducing inequality. But what are the best institutional means to provide this expanded vision of fundamental rights? This paper argues that we must stop expecting or hoping that highly centralized state and corporate institutions, which reserve rights to ownership and control for the few, will produce any results other than those that benefit the few. I argue that in order to provide an expanded vision of fundamental rights we must create a democratic political economy comprised of institutions that are themselves democratic and controlled by the people they are meant to serve. Guided by Karl Polanyi's insight that the fictitious commodification of labor, land, and money has made human society an accessory of the economic system, I propose a vision for creating, starting at the city level, democratic systems for controlling land, labor, and money. The vision--inspired by global movements including the Zapatistas in Mexico, the Movement of Landless Workers in Brazil, the Kurds in Rojava in Northern Syria, and the municipalist movement in Spain--calls for democracy in the workplace through worker cooperatives, local democratic ownership and control of land through land banks, community land trusts, and a land value sales tax, and democratic banking through public banks at the city level. By demonstrating the viability of democratic political economy institutions at the local level, organizers can amass resources to build toward broader systemic transformation.
Keywords: fictitious commodification; fundamental rights; green new deal

Correlated ownership: Polanyi, Commons, and the property continuum - Frerichs, Sabine; James, Rick (Research Handbook on the Sociology of International Law, 2018)
According to the economic analysis of law, an efficient property regime is premised on the universality, the exclusivity, and the transferability of property rights. Ideally then, every (legal) person can enjoy the status of an owner and any (economic) resource can become private property; ownership titles could be bought and sold across national jurisdictions and would ultimately be respected everywhere in the world. Throughout history, property regimes indeed seem to have moved towards this ideal. However, this conception of private property is far less natural than it seems, and not without problems. Instead, the institution of property rights is inherently connected with the development of capitalist society, and it reflects the latter’s underlying tensions. The starting point for a sociological account of property rights is to conceive them as a social relation, or a relation of power, which includes (other) owners and non-owners as well as the state as a ‘third party’. In this chapter, the authors build on the work of Karl Polanyi and John R. Commons to suggest that the property regime of the market society relies both on the reification of property (identifying it with the thing owned) and the commodification of the right of ownership (turning it into a marketable commodity). Looking back, the authors retrace how the concept of property changed with the advent of modern capitalism, and how it evolved in the transition from agricultural to industrial capitalism. Looking into the future, they also address the challenges of today’s informational capitalism, which is characterized by the commodification of knowledge. Based on James’s work, the authors introduce the ‘correlative rights doctrine’ as an alternative to the remnant ‘property rights absolutism’ in the field of intellectual property law, but also beyond. With cross-border conflicts in who owns what having proliferated in the global age, investigations into the relational quality of property rights also matter for international lawyers, who are confronted with new subjects and objects of property, from international investment law to intellectual property law.
Keywords: COMMONS, J.R.; international law; property rights

A Theoretical Note on Commodification of Labour Power in China and the Global Putting-Out System - Westra, Richard (Journal of Contemporary Asia, 2018)
This article captures China's role in global manufacturing through the prism of conceptualisation of the commodification of labour power in Marxist theory. It argues that modalities of China's labour force co-optation in assembly and lower value added production for export of consumer goods to advanced economies carries more of a family resemblance with putting-out systems of the pre- capitalist era than with the commodification of labour power sensu stricto marking the capitalist era from the mid-nineteenth century.
Keywords: China; MARX, Karl, 1818-1883; POLANYI, Karl, 1886-1964; capitalism; commodification; commodification of labour power; consumer goods; global value chains; globalization; international trade; labour supply; manufacturing industries; putting-out system; value chains

Reconstructing Karl Polanyi: Excavation and Critique - Neelakandan, Sanil M. (Capital & Class, 2018)
Keywords: DALE, Gareth; POLANYI, Karl, 1886-1964; Reconstructing Karl Polanyi: Excavation & Critique (Book); economists; nonfiction

The Great Recurrence: Karl Polanyi and the crises of the European Union - Goldmann, Matthias (European Law Journal, 2017)
In his seminal 1944 book The Great Transformation, Polanyi describes the rise and fall of liberal capitalism during the long nineteenth century. Many have realised that Polanyi has a lot to tell about the European Union in the aftermath of the financial crisis. The paper begins with an overview of Polanyi's historiography of the failure of nineteenth-century liberal capitalism and his account of the four elements that helped liberal capitalism thrive, while precipitating its collapse-the idea of the self-regulating market, the gold standard, international peace and liberal constitutionalism. Thereafter, the paper describes the particular transformations that these four elements underwent in the course of European integration and after the financial crisis, with a particular focus on the case law of the Court of Justice. The paper argues that their current constellation has a destructive potential that exceeds the economic dimension of the Union and might pave the way for a much greater failure, one that might defeat Europe's greatest success: the establishment of peace. Ultimately, the paper assesses current reform proposals in light of these insights and makes a number of proposals for re-embedding the economy in society.
Keywords: European Union - politics & government; European Union countries; Great Transformation, The (Book); capitalism; embeddedness

It's not the Cases, It's the System - Koskenniemi, Martti (Journal of World Investment & Trade, 2017)
M. Sornarajah's recent analysis of investment arbitration as an offshoot of 'neoliberalism' is basically correct. But it attaches too much importance to the bias of the arbitrators and the procedural problems in arbitral practice. The controversy over the Trans-Pacific Partnership (TPP), the Transatlantic Trade and Investment Partnership (TTIP) and investment arbitration generally is not about the niceties of arbitral procedure, the discretion of arbitrators or the pros and cons of the European Union proposed 'investment court'. The significance of investment arbitration has to do with the many ways in which already the very presence of a 'dis-embedded' and one-sided system of claims automatically skews public policies in favour of foreign investors. The juristic debate is but the surface of struggle over the role of public power and democratic governance of domestic and global economy.
Keywords: General Agreement on Tariffs and Trade (GATT); Sornarajah; Trans-Pacific Partnership (TPP); Transatlantic Trade and Investment Partnership (TTIP); World Trade Organization (WTO); arbitration & award lawsuits; fair and equitable treatment; investment arbitration; investments - lawsuits & claims; neoliberalism

Lawyers’ Empire and The Great Transformation - Harris, Douglas C. (International Journal of the Legal Profession, 2017)
A literary criticism of the book "Lawyers' Empire: Legal Professions and Cultural Authority" by Canadian lawyer W. Wesley Pue is presented. It outlines economic historian Karl Polanyi's assumption of Great Transformation in Western Europe that made the period of Pue's book long. It examines lawyers being innovators in Canada.
Keywords: Canada; Lawyers' Empire: Legal Professions & Cultural Authority (Book); PUE, W. Wesley; Western Europe; lawyers

The Copenhagen Turn in Global Climate Governance and the Contentious History of Differentiation in International Law - McGee, Jeffrey; Steffek, Jens (Journal of Environmental Law, 2016)
The 2009 Copenhagen Accord marked a significant shift in global climate governance which has been substantially adopted in the 2015 Paris Agreement. At Copenhagen, binding targets for states to reduce emissions were replaced by voluntary pledges. We argue that the Polanyian 'double movement' offers a useful lens to understand the Copenhagen shift in global climate governance as part of ongoing contestation in the international law system between principles of economic liberalisation and redistributive intervention. In the second half of the 20th century, redistributive design of international legal institutions became evident in a number of issue areas including trade law, oceans law and the seminal climate treaties. However, there has been ongoing US lead opposition to 'redistributive multilateralism' (RM), particularly over the last decade of climate negotiations. The Copenhagen model of voluntary pledges, therefore, needs to be viewed as an outcome of this opposition to RM and a related weakening of differentiation in international environmental law.
Keywords: Copenhagen; Copenhagen Accord; UNFCCC; climate change; differentiation of duties; environmental justice; environmental law; international cooperation; international law; political economy; regime design

Economy, Society and Earth in Polanyian and Wild Law Perspectives on Environmental Regulation: To Perform a Double or Triple Movement? - Pontin, Ben (Journal of Environmental Law, 2016)
Keywords: BURDON, Peter D.; HAINES, Fiona; LANGE, Bettina; MALONEY, Michelle; Regulatory Transformations: Rethinking Economy-Society Interactions (Book); THOMAS, Dania; Wild Law: In Practice (Book); book review; double movement; environmental law; nonfiction; triple movement

Proprietary Law Schools and the Marketization of Access to Justice - Tejani, Riaz (Social Science Research Network, 2016)
The rise of for-profit law schools in the United States highlights the interplay of political and moral economy in the reproduction of legal expertise. This article offers ethnographic evidence from one ABA-accredited for-profit law school pseudonymously labeled New Delta School of Law. The article posits New Delta as a case study in market fundamentalism of the kind first theorized by Hungarian economist Karl Polanyi. Polanyi defined global capital as a “double movement” between free marketeerism on the one hand and countervailing social protectionism on the other. Treating this as incomplete, social philosopher Nancy Fraser has since argued that the emancipatory new social movements form a third element in what should more properly be considered a “triple movement.” In this article, I argue that for-profit law schools such as New Delta support Fraser’s revision. Drawing in capital commitments from large institutional investors with promises of high returns on the basis of guaranteed federal student loan dollars, New Delta recruits disproportionately from minority and low-income communities while offering low chances of bar passage and legal employment. By marrying free marketeerism with the discourse of emancipation, the school has successfully evaded scrutiny.
Keywords: anthropology; economic; finance; law; legal education; markets; morals; neoliberalism; race; regulation; triple movement

Regulatory Transformations: Rethinking Economy-Society Interactions - Lange, Bettina; Haines, Fiona; Thomas, Dania (Bloomsbury Publishing, 2015)
The issue of whether transnational risk can be regulated through a social sphere goes to the heart of what John Ruggie has described as 'embedded liberalism': how capitalist countries have reconciled markets with the social community that markets require to survive and thrive. This collection, located in the wider debates about global capitalism and its regulation, tackles the challenge of finding a way forward for regulation. It rejects the old divisions of state and market, citizens and consumers, social movements and transnational corporations, as well as 'economic' and 'social' regulation. Instead this rich, multidisciplinary collection engages with a critical theme-the idea of harnessing the regulatory capacity of a social sphere by recognising the embeddedness of economic transactions within a social and political landscape. This collection therefore explores how social norms, practices, actors and institutions frame economic transactions, and thereby regulate risks generated by and for business, state and citizens.A key strength of this book is its integration of three distinct areas of scholarship: Karl Polanyi's economic sociology, regulation studies and socio-legal studies of transnational hazards. The collection is distinct in that it links the study of specific transnational risk regulatory regimes back to a social–theoretical discussion about economy–society interactions, informed by Polanyi's work. Each of the chapters addresses the way in which economics, as well as economic and social regulation, can never be understood separately from the social, particularly in the transnational context.Endorsement'This thought-provoking collection asks the most critical question of our time – how to civilise markets through social accountability and political action. The climate and financial crises we face show how crucial this challenge is. Lange, Haines and Thomas have put together a series of fruitful case studies of the possibilities for embedding economic relationships in social relationships by a series of top-class researchers within their own illuminating and sensitive framing of the issue'.Professor Christine Parker, Professor of Regulatory Studies at Monash University.
Keywords: administrative law & regulatory practice; economic regulation; economic sociology; embedded liberalism; social regulation; socio-legal studies

Karl Polanyi and the Problem of Corporate Social Responsibility - Moncrieff, Lilian (Journal of Law and Society, 2015)
This article considers Corporate Social Responsibility (CSR) as part of the projects in ‘new governance and decentred regulation’, which draw social forces towards the regulation of economic behaviour. It uses Karl Polanyi to open up pertinent interfaces between society and economy for observation, and Gunther Teubner to substantiate a ‘regulatory’ view of the company's social relationships. The article finds that CSR combines movements for the recognition of social relationships, on an unprecedented scale, with rigorous simultaneous movements for market building and social abstraction. Twenty-first-century market economy is defined by a capacity to contain ‘the social,’ which is thrown between the two movements, creating opportunities for companies to void the market's social limits. The article counterposes that the social that ‘returns’ after marketization needs to find its way past market-building CSR, to constructively unshackle and redefine the framing of social conflicts that concern the corporation.
Keywords: CSR; corporate social responsibility; marketization

Authoritarian Liberalism in the European Constitutional Imagination: Second Time as Farce? - Wilkinson, Michael A. (European Law Journal, 2015)
The current crisis in Europe recalls the theory and practice of authoritarian liberalism, the idea that in order to protect economic liberalism and respect for fiscal discipline, representative democracy must be curtailed. This configuration was first identified by Hermann Heller in late Weimar as a response to the imperative to maintain the ideological separation of state and economy and presented by Karl Polanyi as conditioned by broader geo-political pressure to maintain the gold standard in the inter-war period. Authoritarian liberalism is now conditioned by conflicting imperatives to maintain the project of the single currency, respect ordo-liberal concerns of moral hazard, and protect 'militant democracy' but only in one country. Does this reflect a broader geo-political disequilibrium, due to tensions between market integration, constitutionalism and democracy?
Keywords: Europe; European Sovereign Debt Crisis, 2009-; HELLER, Hermann, 1891-1933; POLANYI, Karl, 1886-1964; authoritarianism; constitutionalism; democracy; equilibrium (economics); liberalism

Law, Fugitive Capital and Karl Polanyi's the Great Transformation - Kendall, Walter J. III (Indonesian Journal of International & Comparative Law, 2015)
Keywords: embeddedness; law and economics; law and society; legal philosophy; legal reform; liberalism

Law and Politics in Europe's Crisis: On the History of the Impact of an Unfortunate Configuration - Joerges, Christian (Constellations, 2014)
EXCERPT [KM]: Karl Polanyi has experienced a renaissance in recent years.13 We refer to his work in our remarks on the failures of the European project for three interrelated reasons: (1) Polanyi has underlined that modern markets were not generated by some evolutionary process but established by political planning.14 Europe's “internal market project” is the best conceivable confirmation of his thesis. (2) One of the most important insights of his work concerns the “social embeddedness” of markets and the economy.15 These insights are of crucial importance because Europe has on the one hand realized that the functioning of markets requires comprehensive regulatory activities but at the same time tends to disregard the economic, political and cultural variety and dependence of markets. (3) Polanyi can also provide clarity with regard to the growing skepticism about so many firmly held beliefs about the benefits of ever more European integration. EXCERPT 2: Led by the prompting of its highest court, Europe is waving the flag of economic freedoms of Europe's market citizens and is retreating from its commitment to collective labor law – once the institutionalized countermovement to the commodification of labor.1
Keywords: European Union; economic law; fictitious commodities; internal market project; social embeddedness

Feminist Reflections on the Scope of Labour Law: Domestic Work, Social Reproduction, and Jurisdiction - Fudge, Judy (Feminist Legal Studies, 2014)
Drawing on feminist labour law and political economy literature, I argue that it is crucial to interrogate the personal and territorial scope of labour. After discussing the “commodification” of care, global care chains, and body work, I claim that the territorial scope of labour law must be expanded beyond that nation state to include transnational processes. I use the idea of social reproduction both to illustrate and to examine some of the recurring regulatory dilemmas that plague labour markets. I argue that unpaid care and domestic work performed in the household, typically by women, troubles the personal scope of labour law. I use the example of this specific type of personal service relation to illustrate my claim that the jurisdiction of labour law is historical and contingent, rather than conceptual and universal. I conclude by identifying some of the implications of redrawing the territorial and personal scope of labour law in light of feminist understandings of social reproduction.
Keywords: decommodification; feminist theory; fictitious commodities; labour law; triple movement

Embedding Trade Liberalisation in Social Policy: A Research Agenda on Social Regionalism and the Global South [article] - Ashiagbor, Diamond (Northern Ireland Legal Quarterly, 2014)
Underpinning this article is the proposition that regional integration with a social dimension has the potential to engender a more equitable pattern of globalisation. The empirical focus of the article is on the ex)tent to which the insights of 'embedded liberalism' associated with regional economic integration between he industrialised nations of the European Union (EU)can be applied to regional economic integration within sub-SaharanAfrica. The article contends that EU market liberalisation has been embedded within labour market institutions and institutions of social citizenship at the domestic level. These have served as social stabilisers to counter the far-reaching effects of the internal market and global trade. Less industrialised nations have never enjoyed adjustment mechanisms of this sort, raising the question for this article, and for further research: in which legal and institutional structures can these nascent forms of market integration at regional and sub-regional level be embedded? In examining the interaction between trade liberalisation and labour standards, I draw on the work of Karl Polanyi. Central to his key work, The GreatTransformation,is the assertion that all economies are enmeshed in non-economic institutions, although the forms and depth of this social embedding may differ. Drawing on Polanyi, I argue that laissez-faire economic liberalism may be offset by principles of social protection at national and, in some instances, regional level - a 'counter-movement' to the economic insecurity arising from globalisation.
Keywords: United Kingdom; social regionism; trade liberalisation

A global theory of justice for new governance : from process to substance with 'parity of participation' - Hermann, Martin (2014)
This thesis proposes a new counter-narrative to the neo-liberal agenda that combines two seemingly disparate bodies of work: New Governance and Nancy Fraser’s theory of justice. New Governance is a new and rapidly growing strand of legal thought and practi ce that has simultaneously developed a following in Europe and the United States. In short, legal scholars in this field of research are advocating a shift away from long-standing command-style, fixed-rule regulation toward more collaborative, bottom-up, and flexible modes of regulation.
Keywords: FRASER, Nancy; neoliberal hegemony; new governance

From Economy to Society: Perspectives on Transnational Risk Regulation - Lange, Bettina; Thomas, Dania; Sarat, Austin (Emerald Group Publishing, 2013)
This special issue asks what role society can play in the regulation of transnational risks, as an alternative to or at least significant addition to reliance on state regulatory activity and the myth of the self-regulatory capacity of markets (Stiglitz, 2001, p. xiii). How can a social sphere contribute to the prevention and management of risks, often transnational in nature, posed by economic activity? Leading socio-legal scholars explore whether and how the idea of harnessing the regulatory capacity of a social sphere provides a new analytical lens that can provide fresh insights into transnational risk regulation, and whether this idea helps to identify innovative approaches to regulating transnational risks. KM - Parts I and II theoretically equgage specifically with Polanyi, and apply and develop Polanyian ideas.
Keywords: administrative law & regulatory practice; commercial law; comparative law; embeddedness; emotions; international law; international trade law; risk; self-regulating market

After a Romantic Aspiration to Society: Harnessing the Regulatory Capacity of a Social Sphere - Lange, Bettina (Studies in Law, Politics & Society, 2013)
This introduction unpacks the key question that informs the articles in this special issue. How does a social sphere inform regulation and, more specifically, how can the regulatory capacity of a social sphere be har-nessed, as an alternative or significant complementary force to state reg-ulation and reliance on the self-regulatory capacity of markets? This question is salient and topical also in light of the search for new regula-tory strategies and perspectives in the aftermath of the 2007 financial and subsequent EU sovereign debt crises, which have led to a major rea-lignment of economy and society in a number of countries. This introduction argues that economic sociology is a crucial reference point for understanding more about the social practices that constitute business behavior. It enables to explore the scope and significance of often interlinked social and legal norms for regulating various transna-tional risks that economic activity can give rise to. The introduction therefore locates the quest for understanding more about the regulatory capacity of a social sphere in debates that draw on Karl Polanyi's analy-sis of the embedding, disembedding, and re-embedding of economic activ-ity into social norms. The introduction highlights one of the key themes developed in this special issue, the idea of society within economy which questions an assumed conceptual distinction between economy and society. This introduction concludes by specifying how the accounts of risk regu-lation developed in this special issue chart a path that is different from recent explorations of the role of a social sphere in regulation, which were conducted under the banner of "the sociological citizen," "regula-tory sociability," and "collaborative governance."
Keywords: European Sovereign Debt Crisis, 2009-; European Union; crisis; economic sociology; economic sociology of law; financial crisis; international business enterprises; regulation; social sphere; socio-legal studies; state regulation; transnational risk

From Polanyi to Discourse Theory - Lange, Bettina (Studies in Law, Politics & Society, 2013)
This article starts from the assumption that economic sociology, including Karl Polanyi's work, can contribute fresh perspectives to regulation debates because it opens up new understandings of the nature of economic activity, a key target of legal regulation. In particular this article examines Polanyi's idea that society drives regulation. For Polanyi the "regulatory counter-movement" is society's response to the disembedding -- in particular through the proliferation of markets -- of economic out of social relationships. Section One of the article identifies three key chal-lenges that arise from this Polanyian take on regulation for contempor-ary regulation researchers. First, Polanyi focuses on social norms restraining business behavior, but neglects social norms embedded in law as also shaping regulation. Second, he seems to imply a clear-cut concep-tual distinction between "economy" and "society." Third, his analysis sidelines the role of interest politics in the development of regulation. Addressing the first of these three key challenges, Section Two of this article therefore argues that a Polanyian vision of "socialized" legal reg-ulation should build on contemporary accounts of responsive law and reg-ulation, which focus attention on social norms informing legal regulation. Section Three of this article tackles the second key challenge raised by Polanyi's work for contemporary regulation researchers, that is, how to transcend a modernist perspective of "economy" and "society" as clearly demarcated, distinct fields of social action. It argues that discourse the-ory is an important alternative theoretical resource. Drawing on Laclau and Mouffe, the article suggests that understanding "economy" and "society" as performed by open and relationally constructed discourses helps to capture interconnections between "economy" and "society" that become particularly visible when we analyze how specific regulatory regimes work at a medium- and small-scale level. These points are further brought to life in Section Four through a discussion of the European Union (EU) regulatory regime for trade in risky, transgenic agricultural products, and in particular the current reform debates about the consideration of the "socioeconomic impacts" of such products.
Keywords: European Union; European Union regulation; discourse theory; economic sociology; embeddedness; embedding theorems; responsive regulation; socio-economic impacts; socioeconomics; transgenic agricultural products

Trust and Regulation: Insights from the Mining Industry - Schiavi, Petrina (Studies in Law, Politics & Society, 2013)
This article develops Polanyi's (2001) theme of harnessing the regula-tory capacity of a social sphere by focusing on trust as an emotion for framing risk regulatory regimes. Using the global mining sector as its focus, it explores the role of trust in the regulation and corporate man-agement of social and environmental risk Sociological perspectives on trust are employed to identify and analyze dynamics of trust in the mining industry. The article draws on data col-lected between 2004 and 2008 by way of participant observation, docu-ment analysis, and in-depth qualitative interviews with around 40 representatives of the mining industry, NGOs, and regulators. Trust-rela-tionships are an example of harnessing the regulatory capacity of a social sphere, but they can also undermine regulatory effort where trust is abused. The effectiveness of trust-based regulation would be enhanced by sanctions for nonperformance that target corporate motivations and financial performance. This research focused on a selection of large, multinational mining corporations with a presence in Australia. Generalizations could not be made from this research about smaller mining entities or single-country or state-owned corporations. A better understanding of corporate trust-building behaviors and motiva-tions can help inform more effective regulatory strategy for improving corporate, social, and environmental impacts. This article contributes to the body of knowledge about the regulation of the social and environmen-tal performance of the mining industry. This is important as many of the remaining accessible mineral deposits across the globe are in areas of environmental and social significance.
Keywords: POLANYI, Karl, 1886-1964; corporate responsibility; delegated legislation; environmental risk assessment; financial risk; mineral industries; mining industry; regulation; risk; social responsibility of business; trust

Sovereign Debt Restructuring in the Eurozone: A Polanyian Reading of Private Law Enforcement - Thomas, Dania (Studies in Law, Politics & Society, 2013)
The social protests ort the streets of indebted sovereigns in crises across the Eurozone have made debt restructuring an imperative. Further delay in achieving this expeditiously and equitably significantly exacerbates the social costs of crises from which current and future generations will struggle to recover. This article examines the feasibility of the drastic and widespread debt restructuring needed to resolve the problem in the face of existing private law sanctions that protect individual creditor rights. It relies on an analysis of US policy in the transition to a securi-tized market and of key sovereign debt cases to reveal the historical con-tingency of private law protections. It concludes by showing that the effectiveness of private law protections have always been constrained by the overriding imperative to achieve debt sustainability with negotiated and consensual workouts. This can be achieved in the Eurozone with stat-utory constraints on enforcement action pending the settlement of debt workouts as suggested in a recent proposal.
Keywords: European Sovereign Debt Crisis, 2009-; Eurozone crisis; Eurozone debt crisis; POLANYI, Karl, 1886-1964; US debt litigation; civil law; contingency theory (management); international finance; private law enforcement; securitization; sovereign bond contracts; sustainability

"Etiquette and Magic": Between Embedding and Embedded Corporate Social Responsibility - Voiculescu, Aurora (Studies in Law, Politics & Society, 2013)
This article looks at corporate social responsibility (CSR) as a discur-sive social practice that attempts to interrogate the global market econ-omy and its neoliberal underpinnings and that reflects as well as frames and shapes domestic and global politics and institutions. Drawing upon Karl Polanyi's notions of reciprocity and redistribution while also emphasizing the normative content of the concept, the article inquires into the position that the CSR discourse occupies in addressing the cor-porate transnational risks derived from social tensions and conflicts and more generally, in answering social expectations for justice. The Polanyian perspective highlights the CSR discursive quest for a missing conceptual consistency and implicitly, for a constructive "critical" core. From this perspective, the article shows CSR to reside within controver-sial conceptual boundaries; a discursive social practice that engages with the social aspiration of embedding market economy in society while it is also in need of reclaiming its critical core and its potential for social change.
Keywords: civil economy; corporate social responsibility; embedding theorems; neoliberalism; reciprocity (commerce); reciprocity and redistribution; social change; social embeddedness; social responsibility of business; socio-legal studies

How Markets Work: The Lawyer's Version - Weidemaier, W. Mark C.; Gulati, Mitu (Studies in Law, Politics & Society, 2013)
This article combines two sources of data to shed light on the nature of transactional legal work. The first consists of stories about contracts that circulate among elite transactional lawyers. The stories portray law-yers as ineffective market actors who are uninterested in designing super-ior contracts, who follow rather than lead industry standards, and who depend on governments and other outside actors to spur innovation and correct mistakes. We juxtapose these stories against a dataset of sover-eign bond contracts produced by these same lawyers. While the stories suggest that lawyers do not compete or design innovative contracts, their contracts suggest the contrary. The contracts, in fact, are consistent with a market narrative in which lawyers engage in substantial innovation despite constraints inherent in sovereign debt legal work. Why would lawyers favor stories that paint them in a negative light and deny them a potent role as market actors? We conclude with some conjectures as to why this might be so.
Keywords: POLANYI, Karl, 1886-1964; contracts; international finance; lawyers; lead industry; socioeconomics; sovereign debt; transactional marketing

Unravelling the Embedded Liberal Bargain: Labour and Social Welfare Law in the Context of EU Market Integration - Ashiagbor, Diamond (European Law Journal, 2013)
European economic integration with a minimalist social policy at EU level was in part made possible by strong domestic labour market and social welfare institutions. The main contention of this paper is that EU market liberalisation was embedded within institutions of social citizenship at domestic level, which served to counter the liberalisation of the internal market. But this settlement has been put under strain. In addition to the challenges posed to the sustainability of European welfare states by the global economic crisis, the internal market jurisprudence of the Court of Justice casts doubt on the sustainability of the ‘embedded liberal bargain’. This paper focuses on the role of the Court, in particular in its jurisprudence on the interaction between (EU) market freedoms and (national) labour law, which undermines the ability of states to retain their regulatory autonomy over labour or social welfare law and, arguably, speeds up the unravelling of the ‘embedded liberal bargain’.
Keywords: European Union; embedded liberal bargain; market liberalisation; market liberalization; social citizenship

Towards an Economic Sociology of Law - Ashiagbor, Diamond; Kotiswaran, Prabha; Perry-Kessaris, Amanda (Wiley-Blackwell, 2013)
Reflecting a developing trend towards interdisciplinary research in economics and law, this agenda–setting volume makes the case for economic sociology of law  an emerging field that draws on empirical, analytical and normative insights from sociology to investigate relationships between legal and economic phenomena. It locates this novel subject in a wider socio–legal tradition and identifies common ground between Polanyian and Weberian approaches to the law, economy, and society, despite the two theorists  divergent views on the functionality of the capitalist model. The volume provides a platform for researchers critical responses to the social embeddedness of market societies. Contributors demonstrate the value of applying a combination of methods in their work, from heterogeneous disciplines such as legal history and ethnography. They consider the position in the western and developed nations, as well as in post–colonial polities. The resulting publication is a well–crafted primer on a specialism that, by combining the insights of socio–economic analysis with the formative influences exerted by their specific legal contexts, informs a more nuanced assessment of law, economics and society.
Keywords: WEBER, Max, 1864-1920; economic sociology; economic sociology of law; law

Rethinking ‘Embeddedness’: Law, Economy, Community - Cotterrell, Roger (Journal of Law and Society, 2013)
Ideas (of Karl Polanyi and others) that economies and markets are ‘socially embedded’ are central to recent research in economic sociology, closely paralleling socio-legal claims for studying law in ‘social context’. But the concept of embeddedness is imprecise and inadequate: a sociology of law and economy cannot rely on it but must address intellectual and moral-political concerns that its use reflects. Max Weber's writings on law and economy have inspired advocates of a new economic sociology of law, but some of Weber's key claims may be outdated, and he treats law and economy as distinct spheres rather than as facets of the social. Sociological research on law and economy should focus on ‘networks of community’ and their regulation, thus illuminating the social character of both law and economic relations. Viewing the social (including economic life) through a ‘community lens’ makes it possible to analyse cultural factors in regulating markets, while emphasizing links between economic relations and other aspects of social life.
Keywords: embeddedness

Law, Social Policy, and the Constitution of Markets and Profit Making - Veitch, Kenneth (Journal of Law and Society, 2013)
This article explores the relationship between law, society, and economy in the context of the contemporary British welfare state. Drawing on themes in Polanyi's The Great Transformation, it identifies the constitutive role of contemporary social policy and law in the creation and maintenance of markets and opportunities for the private sector in the field of welfare, focusing on the institutional mechanisms being put in place to encourage this. What emerges is a reformulation of the function of the welfare state and related law, as these are no longer predominantly driven by a logic of social protection via redistribution to those in need, but increasingly reflect the state's desire to create openings for the private sector within welfare. The institutions that once contributed to ensuring the embeddedness of the market economy in society now play an important role in processes of disembedding – with potentially detrimental consequences for those seeking assistance from the welfare state.
Keywords: Great Britain; disembeddedness; welfare state

Globalization and the Privatization of Welfare Administration in Indiana - Aman Jr., Alfred C. (Indiana Journal of Global Legal Studies, 2013)
This article explores the relationship of globalization to domestic law in the context of privatized welfare services in Indiana. It examines the ways that privatization can affect vulnerable populations such as welfare recipients by, in effect, partially dis-embedding the market from the state. It applies Karl Polanyi's conception of a double movement to illustrate how the political process can, in effect, re-embed the market in the state. Utilizing Indiana's recent experiences with welfare administration privatization, this article shows that re-embedding is not a simple question of reversing decisions already taken, but rather a complex sequencing of political and legal engagements. It recommends law reforms aimed at more easily triggering the kinds of political actions anticipated by Polanyi's analysis.
Keywords: GLOBALIZATION; INDIANA; Indiana; POLANYI, Karl, 1886-1964; POLITICAL participation laws; PRIVATIZATION; Public welfare; double movement; global legal studies; globalization; political participation laws; privatization; public welfare

A Crisis of Executive Managerialism in the EU: No Alternative? - Joerges, Christian; Weimer, Maria (Maastricht Faculty of Law Working Paper No. 2012-7, 2012)
Against a backdrop of rapidly evolving crisis management in the European financial and sovereign debt crisis this essay aims both to explore and to re-consider the role of law in the EU integration process: What did law accomplish? Where did it fail? What is law going to endure? What kind of future can it envisage? The essay traces back the evolution of the law-politics relationship in both EU legal scholarship and practice from the foundational period of ‘integration-through-law’ to the advent of ‘new governance’ in the EU, and finally to the current deep transformations of EU law in new economic governance and the financial crisis. The centrality of law as ‘both the object and the agent’ of European integration, and the legal enshrinement of EU’s economic constitution has recently neglected the weight of ‘the social’ in the societies of post-war Europe, a failure which was to become detrimental to both domestic social stability and the legitimacy of integration. Attempts to cure Europe’s social deficit by re-conceptualizing the notion of law as new governance have widened the theoretical perspective of EU legal scholarship. Yet new governance has not delivered more social democracy and justice in Europe in practical terms, and continues to suffer from the methodological problems of its ‘definition-by-contrast.’ These problems re-emerge in current new economic governance, which Europe’s crisis management is generating. This hybrid arrangement of hard and soft law instruments has, to date, been economically unsuccessful and socially disastrous, especially in the South of Europe. Equally disquieting, the notion of democratic law (either in traditional or experimentalist understandings) has been replaced by a praxis of authoritarian executive managerialism. The essay concludes by sketching out an alternative understanding of law-mediated legitimacy in the integration process, namely ‘conflicts-law constitutionalism’. This approach stresses the normative value of conflicts and pluralism in the process of European integration. Instead of ‘ever more Europe’ it aims to secure the existing democratic credentials of EU law, namely its ability to correct the democratic deficit of the Member States while respecting their constitutional integrity.
Keywords: EU economic constitution; EU financial crisis; European Union; governance; unity in diversity

Polanyi's Embeddedness and Shareholder Stewardship: A Contextual Analysis of Current Anglo-American Perspectives on Corporate Governance - Talbot, Lorraine E. (Social Science Research Network, 2012)
Polanyi saw the economy as properly embedded in society and argued that the capitalist free market, in commodifying social relations of production, seeks to disembed the economy from society. The resulting lack of continuity between society and economy, he maintained, created conflict which necessarily required state intervention. The market economy, therefore, in contrast to neoclassical/neoliberal economics’ vision of an autonomous, self-regulating market, required more, not less, state intervention to sustain it than alternative, more embedded economies. This article explores this conflict in the context of a specific neoliberal claim: that institutional shareholders are capable of being good “stewards” of the companies in which they invest. Utilising Polanyi’s embeddedness, this article assesses the “stewardship” approach as it is manifested in the US and in the UK. This approach is posited on a vision of a disembedded, self-regulating market. Putting it into practice is thus a retrograde step which will only exacerbate the problems created by the market-based corporate governance strategies which have prevailed since the late 1970s onwards.
Keywords: Polanyi; conflict; crisis; embeddedness; shareholder stewardship

Reconfiguring the Politics–Law Relationship in the Integration Project through Conflicts–Law Constitutionalism - Everson, Michelle; Joerges, Christian (European Law Journal, 2012)
This paper argues that the relationship between law and politics must be reconfigured within the European Union. Dissecting recent crises in economic, social and political organisation within Europe with reference to the three ‘fictitious’ commodities of Karl Polanyi, we find that law in Europe has contributed to de-legalisation, de-socialisation and disenfranchisement. Moving on to review the potential for law to respond to crisis through new paradigms of conflict resolution as suggested by Ralf Dahrendorf, we find that the steering capacity of law is nevertheless limited if it fails to establish a sustaining relationship with politics. Our conclusions are modest: conflict–law constitutionalism cannot solve Europe's many crises. However, it does represent a new paradigm of law within which relations between European law and European politics might be re-established—a vital step to overcoming crisis.
Keywords: European Union; constitutionalism; economic law; fictitious commodities

Processes of disembedding and displacement: anomie and the juridification of religio-ethnic identity in post-New Order Bali - Ramstedt, Martin (Asian Ethnicity, 2012)
This article applies Karl Polanyi's observation of a double movement of law in the history of nineteenth and early twentieth-century Europe to an analysis of Bali's integration into the global cultural economy. It describes how the increasing disembedding of the island's tourist industry from local norms and institutions, and the parallel disjuncture between Balinese religiosity and Indonesian state religion have created a condition of increasing collective anomie that has in turn provoked endeavors to juridify the Balinese religio-ethnic identity. Conceding the partial success of the juridification process that has been facilitated by the recent governance reform, and that has indeed effected a significant degree of re-embedding both tourism and religion into local culture, the article argues that not only has the anomic condition not been attenuated; the potential for internal conflict and division has even been enhanced.
Keywords: Bali; Balinese (Indonesian people); Europe; POLANYI, Karl, 1886-1964; anomie; decentralization; decentralization in government; disembedding; ethnicity; identity; juridification; religiousness

Shareholder Engagement in the Embedded Business Corporation: Investment Activism, Human Rights, and TWAIL Discourse - Dhir, Aaron (Business Ethics Quarterly, 2012)
The expansion of extractive corporations’ overseas business opera-tions has led to serious concerns regarding human rights–related impacts. As these apprehensions grow, we see a countervailing rise in calls for government interven-tion and in levels of socially conscious shareholder advocacy. I focus on the latter as manifested in recent use of the shareholder proposal mechanism found in corporate law. Shareholder proposals, while under-theorized, provide a valuable lens through which to consider the argument that economic behaviour is embedded within so-cial relations. In doing so, I situate my analysis within Third World Approaches to International Law (TWAIL) scholarship. Elsewhere, I have supported the use of corporate law tools in advancing the international human rights enterprise and argued that investment activism can be an essential component of this advancement. This paper represents a reflexive pause. Using the case study of a recent proposal submitted to Goldcorp Inc., I seek to problematize the shareholder proposal as a human rights advocacy tool and to examine it as a site of contestation.
Keywords: Third World Approaches to International Law; corporate accountability; corporate law; law; shareholder rights

The Embedded Firm: Corporate Governance, Labor, and Finance Capitalism - Williams, Cynthia A.; Zumbansen, Peer (Cambridge University Press, 2011)
The globalization of capital markets since the 1980s has been accompanied by a vigorous debate over the convergence of corporate governance standards around the world towards the shareholder model. But even before the financial and economic crisis of 2008/2009, the dominance of the shareholder model was challenged with regard to persisting divergences and national differences in corporate law, labor law and industrial relations. This collection explores this debate at an important crossroads, echoing Karl Polanyi's famous observation in 1944 of the disembeddedness of the market from society. Drawing on pertinent insights from scholars, practitioners and regulators in corporate and labor law, securities regulation as well as economic sociology and management theory, the contributions shed important light on the empirical effects on the economy of the shift to shareholder primacy, in light of a comprehensive reconsideration of the global context, policy goals and regulatory forms which characterize market governance today.
Keywords: business & economics / management; corporate governance; disembeddedness; international law; political science / public policy / economic policy

Batas, Katarungan, at Kalikasan: Isang Kritikal Na Pagmuni Sa Ekolohiya at Lipunan - Batongbacal, Jay L. (Social Science Diliman, 2011)
This article is a commentary and critique of the concept of 'environmental justice' that lately has become much more prominent in discourses on the environment, especially in the debates and advocacy on climate change. After briefly considering the origins of the concept, it is argued that environmental justice is limited by its liberal democratic roots--it is an extension of a discourse that ultimately is based on atomism, centralization of power, and legitimization of the marginalization of groups from true democratic decision-making processes. This arises from the absence of a coherent philosophy and system of principles that can balance social demands for access and allocation of resources against individual proclivities toward unending appropriation and accumulation, preventing 'environmental justice' from addressing the counter-environmental effects of consumerism and displacement. To offer an alternative called 'ecological social justice', a reconsideration of the environment within Karl Polanyi's definition of economy and critique of the market society is correlated with the definition of 'social justice' and the right to a healthy environment in Philippine jurisprudence.
Keywords: Philippine jurisprudence; Philippines; atomism; climate change; climatic changes; consumerism; decision making; democracy; ecological social justice; ekolohikal na katarungang panlipunan; environment; environmental ethics; environmental justice; katarungang panlipunan; market society; social justice

Embedding Economic Relationships through Social Learning? The Limits of Patient and Public Involvement in Healthcare Governance in England - Vincent-Jones, Peter (Journal of Law & Society, 2011)
The strategy for NHS modernization in England is privileging individual choice over collective voice in the governance of healthcare. This paper explores the tension between economic and democratic strands in the current reform agenda, drawing on sociological conceptions of embeddedness and on theories of reflexive governance. Building on a Polanyian account of the disembedding effects of the increasing commercialization of health services, we consider the prospects for re-embedding economic relationships in this field. An analysis is provided of the limits of the present legal and regulatory framework of Patient and Public Involvement (PPI) in establishing the democratic and pragmatist conditions of social learning necessary for effective embedding. We show how the attainment of reflexive governance in the public interest is dependent on such conditions, and on the capacities of patients and the public to contribute to debate and deliberation in decision making, including on fundamental policy questions such as how services are provided and by whom.
Keywords: Great Britain; National Health Service; disembeddedness; embeddedness; medical care; public interest; social learning

Karl Polanyi, Globalisation and the Potential of Law in Transnational Markets - Joerges, Christian; Falke, Josef (Hart, 2011)
The patterns and impact of globalization have become a common concern of all international jurists, sociologists, political scientists, and philosophers. Many have observed the erosion of the powers of nation states and the emergence of new transnational governance regimes, and seek to understand their internal dynamics, re-regulatory potential, and normative quality. Karl Polanyi's seminal book - The Great Transformation - is attracting new attention to such endeavors, mirroring a growing sensitivity to the social and economic risks of dis-embedding politics. Their re-construction by Polanyi - including his warning against a commodification of labor, land, and money - provide the trans-disciplinary reference point for the contributions to this book. Political economy, political theory, sociology, and political science inform this discussion of Polanyi's insights in the age of globalization. Further theoretical essays and case studies look at his 'false commodities': money, labor (and services), and land (and the environment). Jurists have hardly ever discussed Polanyi, and the law has not been taken very seriously among 'Polanyians.' It is nevertheless clear that economic stability and social protection are simply inconceivable without the visible hand of law. The legal discussion in this book's concluding chapters do not, and cannot, depart directly from such premises. The framework of their analyses is, instead, informed by current debates on the emergence of para-legal regimes, the fragmentation of international law, and the prospects of constitutional perspectives within which the rule of law and the notion of law-mediated legitimate governance are established. Polanyi's notion of the co-originality of dis-embedding moves and re-imbedding countermoves can, however, be usefully employed in the re-construction of the sociological background of the moves and tensions which jurists discern.
Keywords: conflict of laws; jurisprudence; law - commercial; political science - history and theory

Reading the Story of Law and Embeddesness through a Community Lens: A Polanyi-Meets-Cotterrell Economic Sociology of Law [article] - Perry-Kessaris, Amanda (Northern Ireland Legal Quarterly, 2011)
In this paper I propose that role of law in Karl Polanyi's concept of the 'always embedded economy' (Block 2003) can be enriched by the application of the lens of community (Perry-Kessaris 2008) developed by Roger Cotterrell (1996-present). I begin with Polanyi's suggestion that economic action and interaction are always 'embedded' in wider social life. Reading through the lens of community, we can be more specific: any actor is at once engaged, to different degrees (from fleeting to stable), in multiple types (whether focusing on instrumental, traditional, affective and/or belief-based action) of social life. I then explore a second, implicit, cornerstone of Polanyi's argument: that analytical and normative approaches to economy may become dis-embedded from wider social life. Reading through the lens of community we can again be more specific: In the transformation to a market society, the analytical and normative approaches that are central to economic actions and interactions are confused with, and privileged over, those that are central to non-economic actions and interactions. This confusion and privileging can have what we might call a performative effect on action and interaction. Finally, I explore Polanyi's story of law as a facilitator both of dis-embedding movements and of re-embedding counter-movements. The application of a law-and-community lens suggests some additional details of that storyline and that there are additional plotlines to be pursued. The practical potential of this Polanyi-meets-Cotterrell economic sociology of law is briefly illustrated with references to two 21st Century cautionary tales: the World Bank's investment climate programme and the 2008 financial crisis.
Keywords: COTTERRELL, Roger; United Kingdom; economic sociology of law; embeddedness; investment climate; law and community

The Idea of a Three-Dimensional Conflicts Law as Constitutional Form - Joerges, Christian (RECON Online Working Paper 2010/05, 2010)
‘Constitutionalisation’ is the key concept in the search for legitimate governance in the European Union and in the international system. This paper suggests the revitalising of a discipline which is widely neglected in European law and international law scholarship. It does not, however, recommend a return to the conflict of laws (private international law) in the traditional sense. The new type of conflicts law that the paper advocates is not concerned with selecting the proper legal system in cases with connections to various jurisdictions. This conflicts law is conceptualised as a response to the increasing inter-dependence of formerly more autonomous legal orders and to the democracy failure of constitutional states which result from the external effects of their laws and legal decisions on foreign systems and on their citizens who cannot understand themselves as their authors. European law has a vocation and many means both to compensate for the democracy failures of member states and to build upon this potential in its constitutionalisation. The conflicts law approach also provides new, albeit more restrained, perspectives at international level. WTO law is used to explore and document its constitutional perspectives. The conflicts law approach is differentiated into three dimensions. With this differentiated fabric, the approach responds to transformation processes which have affected contemporary law at all levels of governance after the rise of regulatory politics and the turn to governance. In its second dimension, conflicts law seeks to constitutionalise co-operative problem-solving under the lead of administrative bodies, while its third dimensions is concerned with both the recognition and the supervision of transnational governance arrangements and para-legal regimes.
Keywords: BLOCK, Fred; Europeanisation; World Trade Organization (WTO); always socially embedded' economy; constitutionalisation; deliberative democracy; economic law; economic sociology; multilevel governance; private international law; rule of law; social embeddedness; social regulation; supranationalism

Movement, Countermovement, and Investment Rules - Schneiderman, David (Conference Papers -- Law & Society, 2010)
This paper examines the extent to which one manifestation of neoliberal transnational legality, represented by the investment rules regime, may be vulnerable to critical resistance in the post-recession environment. If the regime was experiencing a crisis of legitimacy before the global recession set in, it might now be portrayed as having broken down entirely. This paper argues, in contrast, that the regime has a constitution-like resiliency that is intended to adapt and last far beyond the present unsettled global scene. First, for many states in the global South, there is no possibility of a Polanyian countermovement without an influx of needed capital from sources such as international financial institutions or foreign investors. This has the effect of locking states further into the regime's web of disciplines. Second, international investment tribunals have been reflexive agents and have responded to legitimacy problems raised by state and social movement actors by adjusting their interpretation of investment treaty disciplines. It turns out that, as Foucault warned, everything is dangerous - states and social movements must move carefully as they proceed to navigate through the current conjuncture. ..PAT.-Unpublished Manuscript
Keywords: Global South; countermovement; global south; investment rules regime; investment tribunals; neoliberal transnational legality

Informal Politics, Formalised Law and the ‘Social Deficit’ of European Integration: Reflections after the Judgments of the ECJ in Viking and Laval - Joerges, Christian; Rödl, Florian (European Law Journal, 2009)
The judgments of the European Court of Justice (ECJ) of December 2008 in Viking and Laval on the compatibility of national collective labour law with European prerogatives have caused quite a heated critical debate. This article seeks to put this debate in constitutional perspectives. In its first part, it reconstructs in legal categories what Fritz W. Scharpf has characterised as a decoupling of economic integration from the various welfare traditions of the Member States. European constitutionalism, it is submitted, is bound to respond to this problématique. The second part develops a perspective within which such a response can be found. That perspective is a supranational European conflict of laws which seeks to realise what the draft Constitutional Treaty had called the ‘motto of the union’: unitas in pluralitate. Within that framework, the third part analyses two seemingly contradictory trends, namely, first, albeit very briefly, the turn to ‘soft’ modes of governance in the realm of social policy and then, in much greater detail, the ECJ's ‘hard’ interpretations of the supremacy of European freedoms and its strict interpretation of pertinent secondary legislation. The conflict-of-laws approach would suggest a greater respect for national autonomy, in particular, in view of the limited EU competences in the field of labour law.
Keywords: BLOCK, Fred; European Union; European constitutionalism; economic law; labour law; social embeddedness

Law as the Interplay of Ideas, Institutions, and Interests: Using Polyani (and Foucault) to ask TWAIL Questions - Fakhri, Michael (International Community Law Review, 2008)
This paper sketches out some preliminary thoughts on political economy that stem from problematics that emerge from TWAIL. The TWAIL story of international law is one of frustration and disappointment because of the constant exploitation of the Third World despite all the historic changes in international legal ideas and institutions, but it also a story of hope in the moments of resistance. In order to better debate how particular international institutions should be changed or whether particular international institutions should be renounced, I suggest that we need to explicate the theories of political economy embedded within these institutions. Drawing from Karl Polanyi's The Great Transformation, bringing alongside the work of Michel Foucault, I sketch out one way of conducting a study of international political economy by suggesting that we can think of law as the interplay of ideas, institutions, and interests.
Keywords: FOUCAULT, Michel, 1926-1984; TWAIL; economics; globalization; international agencies; international cooperation; international institutions; international law; international political economy; law

A New Alliance of De-legalisation and Legal Formalism? Reflections on Responses to the Social Deficit of the European Integration Project⋆ - Joerges, Christian (Law and Critique, 2008)
This paper will cover a wide range of issues. It will start with a reconstruction of the European Community’s ‘social deficit’, arguing that a credible response to this deficit would be a pre-condition for the democratic legitimacy of the deepened integration project. Such a response can be developed in a re-conceptualisation of European law as a new type of supranational/trans-statal conflict of laws – this is the thesis defended in the second section. This vision is contrasted in the third section, first with the steps towards Social Europe envisaged in the Draft Constitutional Treaty, and then with the messages of the recent judgments of the European Court of Justice (ECJ) in Viking and Laval. It goes without saying that the theoretical premises of the argument, let alone its many interdisciplinary dimensions and empirical background, can often only be signalled, but not developed systematically. " I wish to submit is that the ‘social embeddedness’ thesis can help us to understand why Europe has developed an ever more sophisticated regulatory machinery entrusted with the management of the internal market – and why the social deficit of the European construction has become a prominent part of the European agenda.
Keywords: Social Europe; conflict of laws; ordoliberalism; social deficit; social embeddedness; socio-economic division; unity/diversity

In the Zone: Street Markets and Street Merchants in Socio-Legal Perspective - Morales, Alfonso (Conference Papers -- Law & Society, 2008)
Typically when we think of street markets we think of chaotic places full of energy and vibrating with danger and opportunity. Traders or governments create markets to meet existing and emergent demands as well as the unintended consequences of other policy decisions. It is this institutional design, this governance, this regulatory process that provides access to the market and organizes the vending space therein. Public and private entities operating in fiscally constrained environments should attend to the variety of ways there are to establish and regulate markets. Municipalities typically assume that a detailed management scheme is the best approach to managing access to markets and organizing the distribution of space, the assumption being that chaos would result in the absence of the state. However, this is not necessarily the case, merchants' can self-organize access to space as well as a stable and flexible spatial order, and this self-organization can minimize costs, improve access, and contribute to social goods and goals associated with having a public market.This article provides an empirical justification for this claim by examining the creation of Chicago's Maxwell Street Market (hereafter the Market), and describing the subsequent changes in the regulatory scheme of that Market. This discussion recalls Polanyi's observation that all markets are regulated, one way or another, but that the forms and character of regulation obviously varies -- and thus this article argues the thesis that even in apparently unregulated markets we will find regulation, self-created, that produces a social order, in this case a stable and flexible order that accommodates a variety of private and public circumstances and goals. Our case is Chicago's Maxwell St. Market, which between 1973 and 1994 resembled unfettered capitalism. An ethnically heterogeneous multitude of street entrepreneurs organized vending space with little violence in the absence of stable, state sponsored, legal expectations. But this self-organization is nested in an overall history of unregulated street commerce in the area, starting in the 1870s, followed by the City government's creation and regulation of the Market in 1912, then a period of regulation lasting 60 years, followed by a radical change in the regulatory regime that produced a self-organized Market for about 20 years, then finally the City recaptured the Market and has regulated it again since 1994. Planners and policy makers will find this case interesting for three reasons: first, it is an interesting history of public markets and planning interests, second, the data indicate how an ethnically heterogeneous population can self-produce a flexible and stable social order and third, planners and policy makers concerned with locally appropriate and economically efficient, combinations of government and self-regulation of economic activities might apply lessons from this case to the large and growing interest in public markets around the country. ..PAT.-Unpublished Manuscript
Keywords: government regulation; markets; municipal government; nation-state; policy sciences

Third Way Labor Law Reform in Chile - Rosado Marzan, Cesar F. (Conference Papers -- Law & Society, 2008)
Latin America is currently undergoing Karl Polanyi's "double movement" at full swing, as most governments of the region are currently experimenting with policies that defy the neoliberal orthodoxy that has been reigning there for almost three decades. One of such governments has been the center-left Concertación governments of Chile, which have been elected since the restoration of democracy in 1990. In addition to poverty alleviation programs, Concertación has been in an ongoing process of reforming the country's labor laws, attempting to restore some of the labor rights existing prior to the 1973 coup, as well as creating new rights and institutions. The labor inspectorate has been strengthened and reformed under the framework of "Latin" systems of labor inspections, which are pedagogical rather than punitive in orientation. Labor courts are also being radically bolstered, providing workers with a renewed legal avenue to enforce their rights. Although the reforms fall short of full restoration of trade union rights, namely national collective bargaining, they do point to a clear break with the "stateless" regulatory, neoliberal model that Chile was once associated with and provide symbolic and intellectual fodder for further reforms in the country and beyond. ..PAT.-Unpublished Manuscript
Keywords: Chile; Latin America; labor laws & legislation; labour laws & legislation; law reform; mixed economy

Conflict of Laws as Constitutional Form: Reflections on International Trade Law and the Biotech Panel Report - Joerges, Christian (Social Science Research Network, 2007)
Hardly anywhere is the trend towards a perfection of transnational governance arrangements and their “legalization” more visible than in international trade. Governance arrangements established through and alongside WTO law are both practically important and theoretically challenging. They do not just organise international trade relations. They also affect national and regional (European) regulatory policies partly directly, partly more indirectly. How can we explain and how should we evaluate their emergence? The WTO system of 1994, which replaced the GATT of 1947, responded to the ever increasing importance of non-tariff barriers to trade. These barriers reflect regulatory concerns especially in the fields of health and safety, consumer and environmental protection. There importance for WTO member is such that they cannot simply be abandoned for the sake of free trade. This is why the responses the new international trade system institutionalised by special agreements concerning on-tariff barriers to free trade such as the Agreement on the Application of Sanitary and Phytosanitary Measures (SPS) and the Agreement on Technical Barriers to Trade (TBT) reflect a politicisation of international trade. Can we conclude that international markets have been re-regulated and that international trade law ensures their “social embeddedness”? The paper seeks yardsticks for an answer to these questions in the debates on transnational constitutionalism. It submits that constutionalisation can and should be based on a conflict-of approach. For its elaboration of this suggestion, the paper first contrasts the jurdification of transnational governance at the European and the international level. It then discusses the WTO panel report on the Biotech dispute. It concludes that the legalisation and judicialisation in that case have remained “thin.” What can be observed is a political rather than a social and legal embeddedness of markets.
Keywords: FOUCAULT, Michel, 1926-1984; Polanyi and Foucault; World Trade Organization (WTO); constitutionalisation; economic law; embeddedness; european governance; international trade; legal embeddedness; legalization; legitimacy; multilevel governance; national autonomy; risk regulation; social embeddedness; transnational governance

Economic Sociology’s Legacy to Corporate Governance, 2004 - Kahn, Faith Stevelman (Conference Papers -- Law & Society, 2004)
This paper explores the intellectual tradition of Max Weber,Emil Durkheim, Joseph Shumpeter and Karl Polanyi — economic sociologists whose work has been largely ignored by corporate governance scholars focused on the more traditional areas of economics. The foundation laid by Weber is the central focus of the paper. Weber's writing in Economy and Society laid the groundwork for an approach to the study of firms and markets that diverges significantly from that in of the neoclassical economic model. Weber viewed firms and markets as being deeply embedded in and inseparable from the larger systems of social values and social structures that make a society durable. He grounded his view of economic action in a view of social action. Social actions are all deliberate (meaning purposive, which would include deliberately passive) acts undertaken in contemplation of others' acts and reactions. Transactions in money are generally social actions, since the value of money is determined by what people will decide to give you for it! Economic actions are constantly ormed by patterns of meaning, systems of power and social systems (the family....) that underlie them. From this perspective, the growth of the firm has as much to do with the need for rationalization and the rational/economic division of labor (esp. in a condition of limited liability) as it does with any immediate reduction of transaction costs. Rationality ( the struggle for meaning and systems that order chaos) is as pressing a force as efficiency. Recent writing in economics has come close to building a bridge back to economic sociology, especially with its interest in the effects (or lack of) trust in economic transacting as well as other "behavioral" variations. Economic sociology pursues these departures from qualitative rationality at the level of social structure, rather than individual psychological aberrancy. This paper tries to broader this more "socially" oriented view of the behavior of human beings in firms and markets. This intellectual background is related to contemporary issues in corporate governance legislation, and especially the Sarbanes Oxley reforms and then the increased demand for independent directors at public companies and mutual funds.
Keywords: DURKHEIM, Emile; WEBER, Max, 1864-1920; corporate governance; economic sociology; social action; social structure; socioeconomics

'Social Market Economy' as Europe's Social Model? - Joerges, Christian; Roedl, Florian (Social Science Research Network, 2004)
Europe continues to search for its - "European" - social model and the search seems to become increasingly urgent. It is no longer just the "democratic deficit", but also and alongside it, the "social deficit" of the EU which needs to be cured. That new concern is, in fact, a rejection of the older answers. According to the ordo-liberal interpretation of the European legal order as an "Economic Constitution" and, successively, in the analyses of the EU as a "Regulatory State", the sphere of social policy was to remain a domain of the nation state. This seems to have become impossible. The Constitutional Treaty, indeed, makes a new commitment: "The Union shall work for a Social Market Economy". This paper submits that this commitment is conceptually a failure, and politically not credible. The Convention preparing the Constitutional Treaty has apparently ignored the meaning of the concept in the form in which it was shaped in Germany's post-war period. This history entails some pitfalls for the Convention's intentions, as the German "Social Market Economy" involved not only a claim of integrating social concerns into the market economy, but also served to restrict claims for instruments of social policy remarkably at the same time. Moreover, the Convention has failed to confer a new and independent content to the concept of the "Social Market Economy", which could help to overcome the concept's ambivalent history, as well as the Union's real "social deficit". The few innovations, the Charter's Fundamental Social Rights and the Open Method of Co-ordination, were incorporated in such modest and non-committal forms that their potential to further the case for "social Europe" seems marginal. The paper concludes that the invocation of the "Social Market Economy" in the Constitutional Treaty is conceptually flawed and is politically an all too risky promise which may raise expectations which it will subsequently fail to deliver.
Keywords: constitution building; economic law; economic policy; governance; social deficit; social market economy; social policy

Debt Abides: A Prolegomena for Any Future Chapter 11 - Ayer, John D. (American Bankruptcy Law Journal, 2004)
This article presents information related to market transactions. As a mode of organization, markets are so pervasive in our own lives that it may be hard to think just how novel and contingent (in geologic time) they may be. It was economist Karl Polanyi who sought to isolate a juncture in this process of "becoming a market", the point at which the idea of the market transaction becomes not just a tool or an instrument, but a central organizing principle of social life. But it is not clear that even Polanyi would have been able to conceive a later stage, a stage in which the market becomes not merely a tool of the firm or an expression of sovereignty, but a substitute for the firm and for sovereignty itself.
Keywords: autonomy (Political science); international law; markets; organization; political science; social interaction

Market Dominance, Crime, and Globalisation - Messner, Steven F.; Rosenfeld, Richard (Social Dynamics of Crime and Control: New Theories for a World in Transition, 2000)
KM: Our point of departure is Karl Polanyi's classic work on the emergence of industrial capitalism and recent studies that further develop Polanyi's insights. We draw on these analyses to pose a fundamental issue confronting all capitalist societies: the need to restrain the market and prevent the economy from dominating other institutional realms. We explain how this general institutional challenge bear specifically on the problem of crime and crime control
Keywords: crime; double movement; globalization; institutional-anomie theory; law

Creativity, Pluralism, and Fictitious Narratives: Understanding IP Law Through Karl Polanyi - Suthersanen, Uma (2022)
For over a century, jurists have debated as to whether IP rights should be extended to this or that output such as photographs, computer programs, products of data aggregation, virtual objects, natural and organic materials, “creative” algorithms, and genes. What is surprising is the continuing and bifurcating discourse landscape: “IP law protects and rewards creativity” versus “IP law protects investment”. This paper suggests that IP law indiscriminately and simultaneously protected all sorts of res emanating from creative and entrepreneurial labour as well as from capital investment. Continued attempts to discuss or adjudicate IP law, policy and reform through strict conceptual silos such as creativity, labour, and investment are doomed narratives.Instead, I invite readers to appreciate that early modern rules in sensu lato were about mixed motivations of reward, investment, recognition, competition, honour, public interest, and more. The implicit suggestion in this paper is that the root cause of continuing legal conundrums today is the failure to appreciate the pattern set out by two related socio-legal mappings: (i) motivations for early rules in relation to creative and entrepreneurial labour and products in Europe; and (ii) the extent to which current IP norms and laws evolved to absorb such myriad motivations over five hundred years. I employ Karl Polanyi’s theory on the commodification of labour, including investment-backed labour, into tradeable, fictitious commodities, where law and property are recognised as vital institutional tools which disembed and re-embed society from/into the economy. Polanyi’s motivation ethos is effective in synthesising the different mapping points to create a pointilliste landscape which, in turn, shows why IP law only makes juridical sense if it is viewed as a pluralistic concept.
Keywords: creativity; intellectual property; pluralism

Pandemic Paradox and Polanyi: Financial Markets Rise, Economies Crash, and Regulators Toss a Coin - Findlay, Mark (2020)
In the pandemic, investors like all responsible citizens share an obligation to keep the community safe. This obligation extends to informed market decision-making which goes beyond self-interest. The current disconnect between financial markets and the economy is a story of two different realities – or perhaps one harsh reality and one expectant gamble. The disconnect cannot just be explained by the different purposes of economic and financial market analysis but rather by the information indicators on which these rely. To forewarn regulators concerned that these two worlds of global wealth generation and growth moving to polar opposite futures, this brief review has these aims:• To reflect on a legal model for financial markets, their regulation and its limitations so that law and finance may be understood as positively relational when considering market sustainability; and then• To suggest that the explanation for this dangerous disconnect can be found in Karl Polanyi’s understanding of fictitious commodities in self-regulating markets, dis-embedding from the social and his propositions for market correction through the double movement.Despite the neoliberal logic to the contrary (where financial markets are deemed only for maximising investor/shareholder profit) financial market regulation should prioritise market sustainability as part of pandemic control policy.
Keywords: disconnect; economy; financial markets; market sustainability and resilience; pandemic crisis; responsible market decision-making

Understanding the (Re-)regulation of Private Renting in England: Karl Polanyi, the Rogue Landlord, the Responsible Tenant and the Decent Home - Carr, Helen; Alcock, Rowan (Contract law and the legislature: Autonomy, expectations, and the making of legal doctrine, 2020)